2004
DOI: 10.1111/j.1523-1755.2004.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Kidney and anemia in familial amyloidosis type I

Abstract: Anemia in FAP type I is a common manifestation. The results clearly suggest a defective endogenous Epo production in the genesis of the anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 21 publications
1
31
0
4
Order By: Relevance
“…The clearance of phosphatidylserine exposing erythrocytes should lead to anemia. Sequelae of amyloidosis indeed include anemia [54][55][56], which may at least in theory result from amyloid induced eryptosis and subsequent clearance of eryptotic erythrocytes from circulating blood. Amyloid binding has been shown to enhance phagocytosis of erythrocytes in the spleen [57].…”
Section: Discussionmentioning
confidence: 99%
“…The clearance of phosphatidylserine exposing erythrocytes should lead to anemia. Sequelae of amyloidosis indeed include anemia [54][55][56], which may at least in theory result from amyloid induced eryptosis and subsequent clearance of eryptotic erythrocytes from circulating blood. Amyloid binding has been shown to enhance phagocytosis of erythrocytes in the spleen [57].…”
Section: Discussionmentioning
confidence: 99%
“…A small number of ATTR V30M cases, especially late-onset cases, may present with heart failure (28). Precocious anemia, unrelated to renal manifestations, is conferred by low erythropoietin levels (29,30). It was suggested that the distal nephron is the major site of erythropoietin production in ATTR (31).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Low EPO production is an early event in FAP TTR V30M and may precede clinical disease [4]. Similarly, medullary involvement can be clinically silent and be present in asymptomatic carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The serum EPO levels were compared with the expected levels, estimated according to the logarithmic regression equation of EPO against Hb in control subjects [4]. An observed/expected ratio was used to evaluate if EPO production is appropriate to the Hb level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation